2007
DOI: 10.1149/1.2409860
|View full text |Cite
|
Sign up to set email alerts
|

Method to Predict Phase Formation and Specific Capacity for Lithium in Codeposited Silicon-Transition Metal Thin Films

Abstract: A modified version of the effective heat of formation ͑EHF͒ model of Pretorius et al. is presented to predict phase formation in codeposited silicon-transition metal films. The EHF model predicts that the first Si-M ͑transition metal͒ phase to form in thin-film diffusion couples is the phase with the most negative EHF at the composition of the lowest temperature eutectic ͑i.e., at the growth interface͒. Combinatorial thin-film libraries of codeposited Si-M produced using the modified composition spread method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 25 publications
3
30
0
Order By: Relevance
“…When cycled back at C/12, the battery provided 360 mAh g −1 which represents about 81% of capacity recovery. However, a recovery of 94% was obtained when the battery was cycled at R.T., which means that the performance of the battery degrades faster when cycled at 60 • C. As for MoSi 2 , this is most probably due to the formation of a thicker SEI that builds up with cycling at higher temperature, or due to the increased degree of Li 15 Si 4 crystallization at 60 • C as opposed to amorphous Li 15 Si 4 , as reported by Fleischauer et al [24]. Fig.…”
Section: Battery Cyclingsupporting
confidence: 53%
See 1 more Smart Citation
“…When cycled back at C/12, the battery provided 360 mAh g −1 which represents about 81% of capacity recovery. However, a recovery of 94% was obtained when the battery was cycled at R.T., which means that the performance of the battery degrades faster when cycled at 60 • C. As for MoSi 2 , this is most probably due to the formation of a thicker SEI that builds up with cycling at higher temperature, or due to the increased degree of Li 15 Si 4 crystallization at 60 • C as opposed to amorphous Li 15 Si 4 , as reported by Fleischauer et al [24]. Fig.…”
Section: Battery Cyclingsupporting
confidence: 53%
“…After 20 cycles, the electrode has a capacity of only 75 mAh g −1 . As reported by Fleischauer et al, the capacity fade for silicon-rich silicides could be related to the increased degree of Li 15 Si 4 crystallization at higher temperature as opposed to amorphous Li 15 Si 4 which is more reactive [24]. It could also be due to the degradation of the electrolyte and the formation of a thicker SEI layer at the surface of the particles.…”
Section: Battery Cyclingmentioning
confidence: 79%
“…1,2 Models have shown that a-Si/inactive alloy could result in ∼22% energy density improvement of cell stack with about 100% volume expansion (compared to 34% improvement with 280% volume expansion). 2 Thus, binary TM-Si alloys (where TM is a transition metal element that is inactive with lithium) such as Cr-Si, Fe-Si, Ni-Si, Mn-Si and Co-Si, [3][4][5][6][7] have been widely studied as negative electrode materials in the last two decades.…”
mentioning
confidence: 99%
“…When made by sputtering or ball milling, such alloys typically form active Si / inactive matrix nanostructured composites, where the inactive matrix comprises a transition metal silicide. 3,7,[10][11][12][13][14][15][16][17][18][19][20][21] Although transition metal silicides are theoretically active with lithium from a thermodynamic basis, 10 most have been found to be completely inactive or have very limited capacity at room temperature. 3,[12][13][14][15][16][17] For instance, Fleischauer et al used a model based on effective heats of formation to explain the capacity behavior of (Fe, Mn, Cr+Ni, Co)-Si alloys.…”
mentioning
confidence: 99%
“…This well predicted the observed alloy capacities. 16,17 In contrast to the above studies, Recently we have proposed a different model to explain the electrochemical behavior of Ni-Si thin films in terms of internal stresses between active and inactive phases. 7 It has been shown that applied stress can significantly affect the potential of the Si voltage curve during cycling.…”
mentioning
confidence: 99%